2006
DOI: 10.4049/jimmunol.176.1.603
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB and Activator Protein 1 Response Elements and the Role of Histone Modifications in IL-1β-Induced TGF-β1 Gene Transcription

Abstract: Abnormal expression of TGF-β1 is believed to play an important role in the pathogenesis of a number of chronic inflammatory and immune lung diseases, including asthma, chronic obstructive pulmonary disease, and pulmonary fibrosis. Gene activation in eukaryotes requires coordinated use of specific cell signals, chromatin modifications, and chromatin remodeling. We studied the roles of the ubiquitous inflammatory transcription factors, NF-κB and AP-1, in activation of the TGF-β1 gene and histone acetylation at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
121
0
5

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 157 publications
(132 citation statements)
references
References 42 publications
6
121
0
5
Order By: Relevance
“…They cooperate to regulate the expression of the TGF␤1 gene upon IL-1␤ stimulation (31). Moreover, it has been reported that Jun or Fos can interact with the p65 subunit of NF-B (44).…”
Section: Discussionmentioning
confidence: 99%
“…They cooperate to regulate the expression of the TGF␤1 gene upon IL-1␤ stimulation (31). Moreover, it has been reported that Jun or Fos can interact with the p65 subunit of NF-B (44).…”
Section: Discussionmentioning
confidence: 99%
“…6 Accordingly, the high levels of 8-isoprostane alongside increased NF-B, AP-1, AP-2, and JNK observed in DOCAhypertensive rats may act in concert with elevated TGF-␤ 1 , fibronectin, and collagen-1 to accentuate the oxidative and fibrotic destruction of cardiac tissues. [3][4][5]7 Interestingly, upregulating the HO system abated these destructive factors and attenuated cardiac lesions, whereas the HO inhibitor, CrMP, exacerbated cardiac hypertrophy. Although many HO inhibitors are nonspecific, CrMP given at a dose of 4 mol/kg is selective against HO.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Moreover, in DOCA-salt hypertension, locally produced aldosterone in cardiac tissue 3 stimulates TGF-␤ 1 , fibronectin, and collagen-1 causing fibrosis and hypertrophy. 4 Because the TGF-␤ 1 gene promoter contains binding sites for NF-〉 and AP-1, 5 crosstalk among TGF-␤ 1 , NF-〉, and AP-1 is envisaged. Thus, the activation of TGF-␤ 1 , fibronectin, NF-〉, AP-1, and JNK may constitute a potent destructive force in hypertension.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These complexes mobilize nucleosomes, allowing the transcriptional machinery better access to the DNA to be transcribed and leading to increased transcription (38). Up-regulation of target genes by IL-1␤ has been linked to increased histone acetylation at AP-1-specific promoter sites (39). Thus, we hypothesized that if the proximal AP-1 sites in the MMP-1 and MMP-13 promoters were targets of LG268-mediated inhibition,…”
mentioning
confidence: 99%